Frailty is independently associated with mortality in 11 001 patients with inflammatory bowel diseases. Issue 2 (14th June 2020) - Kochar, Bharati; Cai, Winston; Cagan, Andrew; Ananthakrishnan, Ashwin N.
Summary: Background: The prevalence of older adults with inflammatory bowel diseases (IBD) is increasing. Frailty is an important predictor of outcomes in many chronic disease states. The implications of frailty have not been well‐delineated in IBD. Aims: To report the prevalence of a frailty‐associated diagnosis and determine the association between frailty and mortality in a cohort of IBD patients. Methods: In a cohort of 11 001 IBD patients, we applied a validated definition of frailty using International Classification of Disease codes. We compared frail IBD patients to those without a frailty‐related code ("fit"). We constructed multivariable logistic regression models adjusting for clinically pertinent confounders (age, gender, race, IBD type, follow‐up, IBD‐related surgery, ≥1 comorbidity in the Charlson comorbidity index [CCI], and immunosuppression use) to determine whether frailty predicts mortality. Results: A total of 675 (6%) IBD patients had a frailty‐related diagnosis. The prevalence of frailty increased with age, rising from 4% in 20‐29 year olds to 25% in patients 90 years or older. The most prevalent frailty diagnosis was protein‐energy malnutrition. The strongest predictors of frailty were non‐IBD comorbidity, all‐cause and IBD‐related, hospitalisations. Frailty remained independently associated with mortality after adjusting for age, sex, duration of follow‐up, comorbidity, need for IBD‐related surgery and immunosuppression (OR: 2.90, 95% CI: 2.29‐3.68). Conclusions: Frailty is prevalent in IBD patients and increases with age. Frailty nearly triples the odds of mortality for IBD patients. Risk stratifying patients by frailty may improve outcomes.